Initiation of Antiretroviral Therapy Restores CD4+ T Memory Stem Cell Homeostasis in Simian Immunodeficiency Virus-Infected Macaques - Cartwright, Emily K; Palesch, David; Mavigner, Maud; Paiardini, Mirko; Chahroudi, Ann; Silvestri, Guido (Journal of virology, 2016)
Treatment of human immunodeficiency virus (HIV) infection with antiretroviral therapy (ART) has significantly improved prognosis. Unfortunately, interruption of ART almost invariably results in viral rebound, attributed to a pool of long-lived, latently infected cells. Based on their longevity and proliferative potential, CD4(+) T memory stem cells (TSCM) have been proposed as an important site of HIV persistence. In a previous study, we found that in simian immunodeficiency virus (SIV)-infected rhesus macaques (RM), CD4(+) TSCM are preserved in number but show (i) a decrease in the frequency of CCR5(+) cells, (ii) an expansion of the fraction of proliferating Ki-67(+) cells, and (iii) high levels of SIV DNA. To understand the impact of ART on both CD4(+) TSCM homeostasis and virus persistence, we conducted a longitudinal analysis of these cells in the blood and lymph nodes of 25 SIV-infected RM. We found that ART induced a significant restoration of CD4(+) CCR5(+) TSCM both in blood and in lymph nodes and a reduction in the fraction of proliferating CD4(+) Ki-67(+) TSCM in blood (but not lymph nodes). Importantly, we found that the level of SIV DNA in CD4(+) transitional memory (TTM) and effector memory (TEM) T cells declined ∼100-fold after ART in both blood and lymph nodes, while the level of SIV DNA in CD4(+) TSCM and central memory T cells (TCM-) did not significantly change. These data suggest that ART is effective at partially restoring CD4(+) TSCM homeostasis, and the observed stable level of virus in TSCM supports the hypothesis that these cells are a critical contributor to SIV persistence. Understanding the roles of various CD4(+) T cell memory subsets in immune homeostasis and HIV/SIV persistence during antiretroviral therapy (ART) is critical to effectively treat and cure HIV infection. T memory stem cells (TSCM) are a unique memory T cell subset with enhanced self-renewal capacity and the ability to differentiate into other memory T cell subsets, such as central and transitional memory T cells (TCM and TTM, respectively). CD4(+) TSCM are disrupted but not depleted during pathogenic SIV infection. We find that ART is partially effective at restoring CD4(+) TSCM homeostasis and that SIV DNA harbored within this subset contracts more slowly than virus harbored in shorter-lived subsets, such as TTM and effector memory (TEM). Because of their ability to persist long-term in an individual, understanding the dynamics of virally infected CD4(+) TSCM during suppressive ART is important for future therapeutic interventions aimed at modulating immune activation and purging the HIV reservoir.